Dendrite-Free Lithium Deposition Induced by Uniformly Distributed Lithium Ions for Efficient Lithium Metal Batteries - Cheng, Xin-Bing; Hou, Ting-Zheng; Zhang, Rui; Peng, Hong-Jie; Zhao, Chen-Zi; Huang, Jia-Qi; Zhang, Qiang (Advanced materials (Weinheim), 2016)
Li dendrite‐free growth is achieved by employing glass fiber with large polar functional groups as the interlayer of Li metal anode and separator to uniformly distribute Li ions. The evenly distributed Li ions render the dendrite‐free Li deposits at high rates (10 mA cm−2) and high lithiation capacity (2.0 mAh cm−2).